A geochemical study of metasomatised peridotite and marid nodules from the Kimberley pipes, South Africa - Waters, Frances Gillian (Department of Geological Sciences, 2023)
A comprehensive study has been made of a large collection of metasomatised peridotite, and MARIO (Mica-Amphibole-ButileIlmenite-Qiopside) xenoliths from the Kimberley pipes, with the aim of obtaining an improved understanding of enrichment processes operating in the sub-continental lithospheric mantle. The metasomatised peridotite suite is divided into garnet peridotites (GP), which contain no texturally equilibrated or primary phlogopite, garnet phlogopite peridotites (GPP), which constitute the most abundant peridotites, phlogopite peridotites (PP) and phlogopite K-richterite peridotites (PKP). Diopside can be present in all four groups. PKP rocks may also contain exotic incompatible element-rich Crtitanates such as lindsleyite and mathiasite, Nb-Cr rutile, ilmenite and armalcolite. Petrographic and chemical evidence presented here suggest that metasomatism increases progressively in the sequence GPGPP-PP-PKP, with the PKP group being richest in Fe, Ti and incompatible elements such as K, Na, Rb, Ba, Sr, Zr, Nb and the LR.EE. Mineral compositions change progressively from the garnet-bearing rocks to the PP and PKP rocks, showing decreases in Al 2o 3 and cr2o 3 contents, and increases in FeO and Tio2 contents. Data from this study show that most PKP and some PP rocks were derived from Al-deficient harzburgites. Other PP rocks probably had garnet-bearing precursors, as they display chemical similarities to GPP rocks, and typically contain aggregates of phlogopitediopside-spinel which are interpreted and modelled as being garnet replacement textures. Pressures and temperatures of equilibration of the peridotites in this study, combined with published experimental mineral stability data, suggest that metasomatism increases in intensity upwards in the subcontinental lithospheric mantle (SCLM) over a considerable depth interval from _170 km to Sr isotope data suggest that the metasomatism is young (1 Ga) have been recorded by Nd isotopes. New and published peridotite mineral and whole-rock Nd and Sr isotopic compositions range from moderately depleted to highly enriched and are interpreted in terms of mixing between variably enriched "ancient" SCLM and young metasomatic fluids with isotopic compositions close to Bulk Earth values. A rnineralogic expression of the ancient enrichments which might suggest that they resulted from older metasornatic events, cannot be clearly identified, but is best represented by enriched Nd-isotopic compositions of nonmetasornatic garnet. Rare phlogopites with low 1 43 Nd/144Nd ratios are interpreted as the product of complex mixing between the young metasomatic fluids and old enriched SCLM, rather than as older phlogopite. A group of unusually diopside-rich peridotites (±Phlogopite, ±ilmenite), are described and discussed. They are probably not directly related to the main group of metasomatised peridotites. Their chemical differences and greater pressures and temperatures of equilibration are consistent with formation by interaction between a diapir of asthenospheric melt and surrounding peridotitic mantle at the base of the SCLM. Comparison with chemical and isotopic data from the literature for Cr-rich "granny-smith" diopside rnegacrysts and glimmerites (phlogopite-diopside-ilmenite aggregates), suggests that they may have close genetic links with the diopside-rich suite. MARIO nodules are modally dominated by phlogopite, Krichterite and diopside, with lesser ilmenite and rutile, and accessory minerals such as calcite, barite and apatite. Olivine is absent, as is (with one exception) orthopyroxene, which serves to distinguish MARIO rocks from highly metasornatised peridotites. Relative modal proportions, textures and grain-size of MARIO rocks vary considerably, both within and between nodules. Textures suggest that they are igneous cumulates. The maximum stability depth of Krichterite restricts their depths of crystallisation to <120km. Data obtained in this study show that MARIO mineral compositions are Fe and Ti rich compared to most peridotites, and are much poorer in Cr, Al, Mg and Ni. Bulk compositions are alkali- and magnesian-rich (K20=4-9 weight%, Mg0=20-25 weight%), with moderate to high concentrations of i ncompatible trace elements. New and published MARIO mineral Nd and Sr isotopic measurements ranges from slightly depleted to highly enriched compositions. They are interpreted in terms of mixing of recent (phlogopite metasomatism is presented. The model proposes that there was recent input of metasomatic fluids at two distinct levels in the sub-continental mantle lithosphere. (1) Deep level fluids were generated at the base of the subcontinental lithosphere between 170-200 km depth - l l I ) possibly evolved from failed asthenospheric melts. The intensity of metasomatism progressively increased as these fluids percolated upwards to _100 km depth, and the GPP and some of the PP rocks were formed. (2) Shallow level metasomatic fluids were evolved during the crystallisation of MA.RID magmas ponded at 60-100 km depth. They were released into the surrounding SCLM, and formed the PKP and some PP rocks. These MA.RID-derived fluids appear to have overprinted the deep-derived metasomatism in places; some PP rocks have metasomatic signatures with characteristics of both events, which is interpreted as evidence for the passage of both types of fluid through them. Various lines of evidence including variations in mineral and whole-rock chemistry, suggest that both types of fluids contained Si, Al, Fetotal, Fe 3+, Ti, ±Ca, incompatible elements such as K, Na, Rb, Ba, Sr, Zr, Nb, V, LREE, s, and possibly F and Cl. The MARIO-derived fluids may have been generally richer in these elements, as the PKP rocks are more intensely metasomatised than even the most metasomatised GPP. u and related PP rocks. The behaviqr of Ba appears to have been different in the two sources/fluids - the deeper-derived fluids produced Ba-rich phlogopites, whereas the MARID magmas and MARID-derived fluids resulted in the formation of Ba-poor phlogopites in MA.RID and PKP rocks. Modelling of fluid compositions using published crystal/melt and crystal/fluid partition coefficients and PKP mineral trace element abundances is inconclusive but suggests that the MARIDderived fluids (and possibly the deep-derived fluids as well), were strongly LREE-enriched with REE patterns comparable to lamproites or kimberlites, and with moderately high Rb and Ba contents. However, inferred concentrations of Sr in the metasomatic fluids are of the order of 1% or more. The PKP rocks have attracted more attention in the literature than the GPP and PP groups, due to their spectacular J metasomatic assemblages. However, it is worth noting that they are relatively rare (~10% of peridotites from the Kimberley pipes). The ¥.LA.RID-derived metasomatism was probably intense, but strongly localised. In contrast the GPP and PP rocks are extremely abundant at Kimberley (_50% and _30% respectively) and were equilibrated over a large depth interval (170-100 km). The deep-derived metasomatism therefore appears to have been much more pervasive, and although less intense (most GPP rocks have 1-2% phlogopite) , it is considered to be a more significant phenomenon in the context of mantle metasomatic processes, especially as it appears to predate host kimberlite formation and emplacement.